Efeito de promotores de brotação na produtividade de Carya illinoinensis em pomares adensados na região central do Rio Grande do Sul - Wertonge, Gerâne Silva (2025)
Carya illinoinensis (pecan) is a multipurpose tree with significant economic importance. However, the production of this species can be affected by irregularities in budburst, flowering, and fruiting, which impacts profitability. To minimize these issues, commercial budbreak promoters can be used to help overcome bud dormancy and stimulate plant development. Despite the potential of these products, their use is still uncommon in Brazil, and there is a lack of studies on the efficiency of these budburst promoters in pecan cultivation, especially concerning artificial dormancy break. This research aimed to investigate the effect of different budburst promoters on pecan cultivars in Rio Grande do Sul, in densely planted orchards in the first production cycles, and their relationship with climatic conditions. Experiments were conducted in two orchards with different cultivars, spacings, and cycles/age of development during the 2022/2023 and 2023/2024 agricultural seasons. The results are presented in two distinct articles, each addressing a specific harvest and its respective climatic conditions. The first (2022/2023) detailed the effects of different budbreak promoters in the two orchards under high temperatures and drought conditions during the flowering and fruit filling period. Dormex® and Levante® were effective in advancing budburst and increasing productivity in Orchard 1, while Budbreaker®, Florvit®, and garlic extract, although not advancing budburst, increased fruiting. In Orchard 2, Levante® and Dormex® increased budburst in only two cultivars, and garlic extract did not increase budburst, but all products contributed to increased fruiting in some cultivars. The second article (2023/2024) analyzed the effects in both orchards under high rainfall conditions, showing that Levante® and Dormex® were more effective in promoting budburst in some cultivars in Orchard 1, with Levante® standing out in promoting fruiting in both orchards. In Orchard 2, Levante® was the main promoter of fruiting with an increase in some cultivars compared to the previous harvest. Additionally, the promoters increased fruiting in the cultivars Success, Barton, Imperial, and Miotto. The comparison between the harvests revealed that the excessive rain in 2023/2024 hindered fruit production in the most productive cultivars of Orchard 1, but the promoters boosted fruiting in cultivars with low production in the previous harvest. Therefore, the research demonstrates that budbreak promoters can be effective in overcoming dormancy and advancing budburst in pecan trees, although production is still lower in the first years of production. However, their efficacy varies according to the cultivar, climatic conditions, and orchard.